Influence of Organic Friction Modifiers on Surface Energy Properties in Polyalphaolefin (PAO) Blends - Lee, Chiew Tin; Ng, Hou Mun; Aaron Edward Sheng, Jye Teo; Wong, Keng Yinn (Penerbit UTM Press, 2025)
The shift towards alternative fuels like hydrogen, ethanol, and other sustainable energy sources drives the need for highperformance lubricants to handle new thermal and chemical challenges. Synthetic polyalphaolefins (PAOs) are commonly utilised due to their thermal stability, high viscosity index, and reliable low-temperature flow. This study investigates the impact of organic friction modifiers—oleic acid (OA) and stearic acid (SA)—on PAO-based lubricants' tribological and interfacial characteristics. Blends containing 0.1–0.5 wt% OA or SA were tested. Contact angle measurements indicated that the 0.3 wt% OA blend significantly improved surface wettability, achieving the lowest contact angles on glass and steel surfaces. Surface energy analysis revealed decreased surface tension and better adhesion for the 0.3 wt% OA blend. Friction testing showed that the 0.3 wt% OA blend recorded the lowest coefficient of friction; however, wear resistance largely remained unaffected. These findings indicate that OA improves frictional performance in PAO lubricants, presenting a promising avenue for optimising formulations for future energy systems